What Should Armies Do? : Armed Forces and Civil Security - Clarke, John L., 1952- (England Ashgate Publishing Limited, 2014)
This volume focuses on two key elements in the North American and European security debate: the decline of both the external threats to most North American and European states, and that of budgetary resources available for defense.
Keywords: Military readiness -- National security -- Armed Forces--Civic action -- Armies--Organization